2021
DOI: 10.1002/1878-0261.13079
|View full text |Cite
|
Sign up to set email alerts
|

Elesclomol induces copper‐dependent ferroptosis in colorectal cancer cells via degradation of ATP7A

Abstract: Cancer cells reprogram their copper metabolism to adapt to adverse microenvironments, such as oxidative stress. The copper chelator elesclomol has been reported to have considerable anticancer efficacy, but the underlying mechanisms remain largely unknown. In this study, we found that elesclomol-mediated copper overload inhibits colorectal cancer both in vitro and in vivo.Elesclomol alone promotes the degradation of the copper transporter ATP7A, which retards the proliferation of colorectal cancer cells. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
155
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(159 citation statements)
references
References 52 publications
3
155
1
Order By: Relevance
“…What's more, the pathway that FDX1 induces tumor cell death has been illuminated in the recent research titled "Copper ionophore-induced cell death" published in the journal Science [17] . Copper death has been proved to be closely related to the progression of many tumors [18][19][20][21] , in which the accumulation of copper in cells results in an overall reduction in proteins involved in mitochondrial respiration, reduced protein lipoylation, and reduced levels of Fe-S cluster proteins. According to the evidence mentioned, there exists a hypothesis that in these cancers FDX1 serves as a protective gene FDX1 launch the mechanism of copper death in the tumor cell.…”
Section: Discussionmentioning
confidence: 99%
“…What's more, the pathway that FDX1 induces tumor cell death has been illuminated in the recent research titled "Copper ionophore-induced cell death" published in the journal Science [17] . Copper death has been proved to be closely related to the progression of many tumors [18][19][20][21] , in which the accumulation of copper in cells results in an overall reduction in proteins involved in mitochondrial respiration, reduced protein lipoylation, and reduced levels of Fe-S cluster proteins. According to the evidence mentioned, there exists a hypothesis that in these cancers FDX1 serves as a protective gene FDX1 launch the mechanism of copper death in the tumor cell.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of 21 different types of cancer in 7462 cancer samples showed that both SLC7A11 and GPX4 are overexpressed in colorectal cancer (CRC) ( 121 ). Elesclomol, a copper chelator, suppresses CRC both in vitro and in vivo by inducing ROS accumulation and is associated with downregulation of SLC7A11 protein levels via ubiquitination and degradation ( 122 ). CRC stem cells have higher levels of cysteine, GSH, and SLC7A11 and, therefore, exhibit lower levels of ROS as compared to CRCs.…”
Section: Gastrointestinal Tract Cancersmentioning
confidence: 99%
“…It was found that CuSO4 could induce ferroptosis through autophagy-dependent degradation of ferritin [ 32 ]. Combinational treatment of elesclomol and copper could lead to copper retention within mitochondria due to ATP7A downregulation through a protein degradation pathway, leading to ROS accumulation, simultaneously ATP7A loss inhibited the interaction between SLC77A11 and CD44, which in turn promoted the degradation of SLC7A11, thus further enhancing oxidative stress and consequent ferroptosis [ 33 ]. Cuprizone (CZ), another copper chelator, could increase the expression of NCOA4, leading to ferritin phagocytosis to release of iron, and iron overload resulting from enhanced iron uptake by high expression of TfR1, thereby induced ferroptosis [ 34 ].…”
Section: Copper Metabolismmentioning
confidence: 99%